Morphometric parameters and food preference in relation to sex and reference hematological values for Upupa epops from Pakistan - Tahir, Rida; Zafar, Warda; Aslam, Muhammad Waseem; Waheed, Ahmad; Umar, Ali; Fatima, Sana; Javed, Tariq; Liaqat, Tabish; Ditta, Allah; Ashfaq, Muhammad; Zaman, Muhammad; Nawaz, Ali; et al. (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The study was conducted to investigate the gut content and record morphometric and hematological parameters in the common hoopoe (Upupa epops). Materials and Methods: Twenty samples of healthy birds (10 from each sex) were collected from different locations in Okara District, Punjab, Pakistan, from September 2020 to March 2021. Birds were captured live for blood samples and morphometric and gut analyses. Results: It was revealed that the concentrations of different hematological parameters were as follows: hemoglobin, 20.03g/dl; red blood cells, 3.28 × 106/µl; white blood cells, 326.67 × 103/ µl; hematocrit, 56.47%; MCV, 173.33 FL; MCH, 57.4 pg; MCHC, 57.4 pg; PLT, 8.33/µl; and RDW, 8.33/µl. The percentages of neutrophils, lymphocytes, monocytes, and eosinophils were 84.67%, 11.67%, 2.00%, and 1.67%, respectively. The gut content of the common hoopoe mostly consisted of Coleoptera and Acrididae larvae. However, Lepidoptera, Gryllotalpidae, and sand were also recorded, along with seeds of Salvadora persica. Conclusions: There were no significant differences between male and female U. epops in feeding content, total weight of the gut, or weight of the empty gut. Regarding the morphometric parameters, there was a significant difference in both sexes’ wingspan, body length, and body weight. Males were significantly heavier than females. J. Adv. Vet. Anim. Res., 9(2): 290–294, June 2022 http://doi.org/10.5455/javar.2022.i595